2011
DOI: 10.1063/1.3621832
|View full text |Cite
|
Sign up to set email alerts
|

Effects of nanocrystal formation on the soft magnetic properties of Fe-based bulk metallic glasses

Abstract: Articles you may be interested inEnhancement of glass-forming ability of Fe-based bulk metallic glasses with high saturation magnetic flux density AIP Advances 2, 022169 (2012); 10.1063/1.4733340Effect of P addition on nanocrystallization and high temperature magnetic properties of low B and Nb containing FeCo nanocomposites

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(20 citation statements)
references
References 17 publications
1
19
0
Order By: Relevance
“…Fe-based nanocrystalline soft magnetic alloys have been extensively investigated in physics [1][2][3] , material science [4] as well as engineering application [5] due to their excellent soft magnetic properties such as low coercivity, low magnetic core loss, high permeability, and high magnetic flux density, compared with conventional materials [6] . They are widely used for various actual applications such as transformers, motors, inductors, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Fe-based nanocrystalline soft magnetic alloys have been extensively investigated in physics [1][2][3] , material science [4] as well as engineering application [5] due to their excellent soft magnetic properties such as low coercivity, low magnetic core loss, high permeability, and high magnetic flux density, compared with conventional materials [6] . They are widely used for various actual applications such as transformers, motors, inductors, etc.…”
Section: Introductionmentioning
confidence: 99%
“…It is well-known that many physical and mechanical properties of MGs can significantly change upon (partial) devitrification [9][10][11]. For example, several studies have indicated that the controlled formation of nanocrystals in an amorphous matrix during heating of some Fe-based MGs can drastically improve their magnetic properties [12,13]. Moreover, a noticeable enhancement in strength and toughness has been obtained in some Al-Ni-based amorphous alloys by partial crystallization via the development of ductile crystals in the amorphous matrix [14].…”
Section: Introductionmentioning
confidence: 99%
“…Alloy ingots with a nominal composition of Fe 75.3 C 7.0 Si 3.3 B 5.0 P 8.7 Cu 0.7 (at. %) [13], hereafter designated as Cu0.7, were prepared by arc-melting a mixture of pure elements (99.9 %) and the Fe-P alloys (P: 26.28, Si:0.01, C:0.02, Mn:0.69, Ti:0.35, Ca:0.01, S: 0.01 wt%) under an argon atmosphere. Ribbon samples with a width of 1-2 mm and a thickness of 30-50 m were prepared by the melt-spinning technique.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, an appropriate annealing below the glass transition temperature (T g ) was verified to further improve the M s value of these Cu-doped Fe-based BMGs, whereas over-aging was found to deteriorate the soft magnetic properties [13][14][15]. As pointed out by Hono et al [14,15], Cu atomic clusters were present in the amorphous state after annealing below the crystallization temperature and gave rise to formation of a high density of tiny α-Fe particles, which might be responsible for the M s enhancement [13][14][15]. Even though effects of Cu additions on heterogeneous nanocrystallization and dependence of magnetic properties on annealing conditions have been investigated in several Fe-based metallic glasses, limited studies regarding the entire dynamic crystallization process were conducted [16,17], especially in those which have a complex atomic structure and nanocrystallization process [18].…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation